The use of wordplay in advertisements published in men’s magazines. A Comparative study in the UK and Spain - Díaz-Pérez, Francisco Javier (Estudios Ingleses de la Universidad Complutense, 2012)
This paper focuses on the use of wordplay in advertisements published in the British and Spanish editions of three well-known men’s magazines, namely Esquire, GQ, and Men’s Health. The function of puns in advertising is explained from the perspective of Relevance Theory. In spite of requiring additional processing effort from the addressee, puns reveal themselves as an economical way of producing additional positive cognitive effects. They also contribute to the creation of a positive attitude towards the promoted product and are useful attention-getting devices. All in all, 208 advertisements were analysed, out of which 49 contained a pun. However, the tendency to use wordplay is higher in the British advertisements than in the Spanish ones, which can be explained by a long tradition of punning in the English-speaking countries and by a higher probability of finding homophones in the English language.